Analysis of elastic behaviour of granite using homogenisation theory - Baek, Y.; Kweon, O. I.; Seo, Y. S.; Kim, K. S.; K im, G. W. (Journal of Nepal Geological Society, 2006)
We carried out photographic analysis of randomly distributed discrete elements in the lnada granite. The modal analysis of granite was also conducted simultaneously with the above photographic analysis. The results show that quartz and feldspar including mica occupy 99.4% of the total volume of the fine-grained granite. Based on the results of previous studies, an elastic homogenisation method is applied to analyse the macro-level stress distribution in the lnada granite, which is a composite material of rock-forming minerals with micro discontinuities. For proper rock sampling and specimen preparation, the representative elementary volume (REV) should be determined in rock mechanical tests and numerical analyses. We determined the REV of the lnada granite using a stereoscopic microscope and applying a homogenisation numerical analysis.